Disentangling the influence of earthworms on microbial communities in sugarcane rhizosphere - Braga, Lucas Palma Perez (2017)
For the last 150 years many studies have shown the importance of earthworms for plant growth, but the exact mechanisms involved in the process are still poorly understood. Many important functions required for plant growth can be performed by soil microbes in the rhizosphere. To investigate earthworm influence on the rhizosphere microbial community, it was performed a macrocosm experiment with and without Pontoscolex corethrurus (EW+ and EW-, respectively) and followed various soil and rhizosphere processes for 217 days with sugarcane. In the second chapter of this thesis it was demonstrate that in EW+ treatments, N2O concentrations belowground (15 cm depth) and relative abundances of nitrous oxide genes (nosZ) were higher in bulk soil and rhizosphere, suggesting that soil microbes were able to consume earthworm-induced N2O. Shotgun sequencing (total DNA) revealed that around 70 microbial functions in bulk soil and rhizosphere differed between EW+ and EW- treatments. Overall, genes indicative of biosynthetic pathways and cell proliferation processes were enriched in EW+ treatments, suggesting a positive influence of worms. In EW+ rhizosphere, functions associated with plant-microbe symbiosis were enriched relative to EW- rhizosphere. Ecological networks inferred from the datasets revealed decreased niche diversification and increased keystone functions as an earthworm-derived effect. Plant biomass was improved in EW+ and worm population proliferated. Considering that earthworms contributed to with extra resources, it was evaluated in chapter three response of the soil resistome of sugarcane macrocosms under the influence of earthworms. Mechanisms of resistance against antimicrobial compounds appear to be an obligatory feature for the ecology and evolution of prokaryotic forms of life. However, most studies on resistance dynamics have been conducted in artificial conditions of anthropogenic inputs of antibiotics into very specific communities such as animal microbiomes. To resolve why and how resistance evolves, it is important to track antibiotics resistance genes (ARGs) (i.e., the resistome) in their natural hosts and understand their ecophysiological role in the environment. The results demonstrated that earthworms influenced changes of ARGs in bulk soil and rhizosphere. Negative correlations between ARGs and taxonomical changes were increased in EW+. Differential betweenness centrality (DBC=nBCEW+ - nBCEW-) values comparing the network models with and without earthworms showed earthworm presence changed the composition and the importance of the keystone members from the models. Redundancy analysis suggested that ARGs may be associated with microbial fitness, as the variance of relative abundance of members of the group Rhizobiales could be significantly explained by the variance of a specific gene responsible for one mechanism of tetracycline detoxification